Vapor deposition substrate, laminate for packaging material, packaging container, and packaged article
Patent Information
- Application Number
- JP2024203433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-01
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-06
AI Technical Summary
When high-content recycling plastics are used in existing packaging materials, problems such as foreign matter, uneven thickness and degradation of gas barrier properties are prone to occur, especially when chemical recycling of plastics are used, surface foreign matter and thermal degradation caused by heat treatment.
A polyolefin film made of chemically recycled plastic is used as a substrate to form a gas barrier layer through vapor deposition, and a solvent free adhesive and cover layer are combined to improve layer uniformity and strength.
It effectively suppresses the decline in gas barrier properties, reduces surface foreign matter and thermal degradation, and improves the quality and strength of packaging materials.
Smart Images

Figure 2025019193000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a deposition substrate, a laminate for packaging materials, a packaging container, and a packaging article. [Background technology]
[0002] Packaging materials used in packaging containers such as packaging bags are required to have various properties depending on the application. Therefore, in order to simultaneously satisfy such various performance requirements, the packaging material is generally composed of a laminate including a substrate and a sealant layer. A known example of such a laminate for packaging materials is a laminate including a first layer including an inner liner and a second layer including an outer sheath, where the outer sheath is made of a post-consumer resin (hereinafter also referred to as "PCR") that may contain contaminants such as paper, ink, food residues, etc. (see Patent Document 1 below). Also known as a laminate for packaging materials is a laminate film that includes at least a recycled polyethylene layer and a linear low-density polyethylene layer, where the recycled polyethylene layer contains 20% by mass or more of material recycled polyethylene relative to the total amount constituting the recycled polyethylene layer (see Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Special Publication No. 2022-552096 [Patent Document 2] JP 2023-040660 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the laminate described in Patent Document 1 above has the following problems when the PCR content is increased in the case where the PCR is a recycled resin containing contaminants, that is, a so-called material recycled resin. In other words, in the laminate described in Patent Document 1 above, foreign matter such as impurities, gels, and aggregates may appear on the surface of the outer sheath, and when a vapor deposition layer is formed on the surface of the outer sheath, the thickness of the vapor deposition layer formed becomes uneven, making it more likely that the barrier properties will be reduced or cracks will occur. Furthermore, in the laminate film described in Patent Document 2, foreign matter may be present on the surface of the recycled polyethylene layer containing recycled polyethylene. When a vapor deposition layer is formed on the surface of the recycled polyethylene layer as a barrier layer against oxygen, water vapor, etc., the thickness of the vapor deposition layer formed becomes uneven, which makes the barrier properties more susceptible to deterioration and cracks.
[0005] An object of the present disclosure is to provide a deposition substrate, a laminate for packaging materials, a packaging container, and a packaging article that are capable of suppressing a decrease in gas barrier properties even when a substrate containing recycled resin is used. [Means for solving the problem]
[0006] One aspect of the present disclosure provides a vapor deposition substrate having a vapor deposition layer formed on a substrate, the substrate being a polyolefin resin film containing a recycled resin, and the recycled resin being a chemically recycled resin. According to the above deposition substrate, the recycled resin used for the substrate of the deposition substrate is a chemically recycled resin, which is produced by first converting a discarded resin into a monomer through a process that is carried out according to the material characteristics, such as a process of converting the resin into a monomer through gasification, oilification, and refined naphtha, or a process of converting the resin into a monomer through depolymerization, and then polymerizing the resin. Therefore, the chemically recycled resin is less likely to be mixed with foreign matter such as impurities, gels, and aggregates, compared with material recycled resin, which is a resin that is made by cleaning and crushing a resin product such as a recovered used packaging material, and then heating and melting it to re-raw material. In addition, unlike material recycled resin, the chemically recycled resin is not affected by heat treatment such as heating and melting after the recycling process, so that it is less likely to be thermally deteriorated, and there is less presence of foreign matter such as gels and aggregates on the surface. Therefore, even if a deposition layer is formed on such a substrate, the thickness of the deposition layer is less likely to be uneven, and a high-quality deposition layer is formed. Therefore, even if the deposition substrate uses a substrate containing a recycled resin, the gas barrier property can be suppressed from being deteriorated. One aspect of the present disclosure provides a laminate for packaging material comprising a vapor deposition base material having a vapor deposition layer formed on a base material, and a sealing layer, wherein the base material is a polyolefin resin film containing a recycled resin, and the recycled resin is a chemically recycled resin. According to the laminate for packaging material, even when a vapor deposition base material in which a vapor deposition layer is formed on a base material containing recycled resin is used, deterioration of the gas barrier property can be suppressed.
[0007] The content of the recycled resin in the laminate for packaging material may be 10% by volume or more or 10% by mass or more. The higher the content (use ratio) of the recycled resin in the laminate for packaging material, the more the environmental load can be reduced. The content of the recycled resin in the laminate for packaging material is generally 10% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, even more preferably 30% by volume or more, and particularly preferably 40% by volume or more. Here, when it is not easy to calculate the mass ratio (mass%) after the laminate for packaging material is made into a packaging material, the unit of the content of the recycled resin may be "volume %" so that it can be calculated by the film thickness ratio. In other words, the ratio of the film thickness of the layer using the recycled resin to the film thickness of the entire laminate can be used as the content (volume %) of the recycled resin. The density of polyethylene and polypropylene that constitute most of the packaging material is 0.86 to 0.97 g / cm 3 The range of the recycled resin content specified in volume percent generally satisfies the range specified in mass percent.
[0008] The above-mentioned laminate for packaging material may further comprise a second substrate on one or both sides of the substrate. In this case, the deposition base material is reinforced by the second base material, so that the strength of the laminate can be further improved.
[0009] In the laminate for packaging materials, the recycled resin may be a post-consumer recycled resin (PCR). PCR can reduce the cost of laminates because large quantities are available on the market. The recycled resin may be a combination of PCR and post-industrial recycled resin (PIR).
[0010] In the above laminate for packaging material, the sealing layer may be a sealant film or a heat seal varnish layer.
[0011] In the above-mentioned laminate for packaging material, the deposition base material and the second base material may be bonded together with a solventless adhesive.
[0012] The laminate for a packaging material may further include an overcoat layer on the vapor deposition layer. In this case, the gas barrier property of the laminate is further improved. Therefore, when the laminate is used to prepare a packaging container and contents are placed in the packaging container, deterioration of the contents due to gases such as oxygen can be effectively suppressed. The packaging laminate further includes an adhesive layer between the base material and the sealing layer, the adhesive layer being an adhesive layer formed using an adhesive, and the adhesive may be a urethane-based adhesive, a polyester-based adhesive, a polyamide-based adhesive, an epoxy-based adhesive, or an isocyanate-based adhesive.
[0013] Another aspect of the present disclosure provides a packaging container obtained by using the above-mentioned laminate for packaging materials. According to the above packaging container, as already described, the chemically recycled resin as the recycled resin contained in the substrate of the laminate is less likely to be contaminated with foreign matter such as impurities, gels, and aggregates than the materially recycled resin. In addition, unlike the materially recycled resin, the chemically recycled resin is not affected by heat treatment such as heat melting after the recycling process, so it is less likely to be thermally deteriorated and there is less presence of foreign matter such as gels and aggregates on the surface. Therefore, even if a deposition layer is formed on such a substrate, the thickness of the deposition layer is less likely to be uneven, and a high-quality deposition layer is formed. Therefore, the packaging container obtained using the above-mentioned packaging laminate can suppress the deterioration of gas barrier properties.
[0014] Yet another aspect of the present disclosure provides a packaging article comprising the above-described packaging container and a content contained within the packaging container. According to the above-mentioned packaging article, as already mentioned, the chemically recycled resin as the recycled resin contained in the substrate of the laminate is less likely to be mixed with foreign matter such as impurities, gels, and aggregates than the materially recycled resin. In addition, unlike the materially recycled resin, the chemically recycled resin is not affected by heat treatment such as heat melting after the recycling process, so it is less likely to be thermally deteriorated and there is less foreign matter such as gels and aggregates on the surface. Therefore, even if a deposition layer is formed on such a substrate, the thickness of the deposition layer is less likely to be uneven, and a high-quality deposition layer is formed. Therefore, a packaging article having a packaging container obtained using the above-mentioned packaging laminate can suppress the deterioration of gas barrier properties. Effect of the Invention
[0015] According to the present disclosure, there are provided a deposition substrate, a laminate for packaging materials, a packaging container, and a packaging article that can suppress a decrease in gas barrier properties even when a substrate containing recycled resin is used. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a packaging laminate according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing another embodiment of the packaging laminate according to the present disclosure. [Diagram 3] FIG. 3 is a cross-sectional view showing another embodiment of the packaging material laminate according to the present disclosure. [Figure 4] FIG. 4 is a cross-sectional view showing still another embodiment of the packaging material laminate according to the present disclosure. [Diagram 5] FIG. 5 is a cross-sectional view of one embodiment of a packaging article according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, preferred embodiments of the present disclosure will be described in detail. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted.
[0018] <<Packaging laminate>> First, an embodiment of the packaging laminate according to the present disclosure will be described with reference to Figures 1 to 4. Figures 1 to 4 are cross-sectional views showing various embodiments of the packaging laminate according to the present disclosure.
[0019] As shown in FIG. 1, a laminate for packaging material (hereinafter also referred to as “laminate”) 100 includes a deposition base 10 and a seal layer 30. 2, the deposition substrate 10 is formed by forming a deposition layer 61 on a substrate 11. Here, the substrate 11 is a polyolefin resin film containing recycled resin, and the recycled resin is a chemically recycled resin. 2 to 4, the laminate 100 may further include an overcoat layer 62 on the deposition layer 61 of the deposition base material 10. A layer constituted by at least one of the deposition layer 61 and the overcoat layer 62 functions as a "gas barrier layer." The laminate 100 may further include a second substrate 20 between the deposition substrate 10 and the sealing layer 30 . The laminate 100 may further include a printed layer 50 as shown in FIG. When the laminate 100 is used for a tube container, as shown in FIG. 3, the laminate 100 may further include an outer sealant layer (also referred to as a “second sealant layer”) 40 on the side of the deposition substrate 10 opposite the sealing layer 30.
[0020] According to the laminate 100, even when a deposition base material in which a deposition layer is formed on the base material 11 containing recycled resin is used, deterioration of the gas barrier property can be suppressed. The content of recycled resin in the packaging laminate 100 is preferably 10% by volume or more or 10% by mass or more.
[0021] <Vapour-deposition base material> The deposition substrate 10 is a member in which a deposition layer 61 is formed on a substrate 11 .
[0022] (base material) The substrate 11 is made of a polyolefin resin film containing recycled resin, and the recycled resin is a chemically recycled resin.
[0023] The polyolefin resin film includes a polyolefin resin film, for example, polyethylene and polypropylene.
[0024] Polyethylene is a resin containing ethylene as a structural unit. Examples of polyethylene include ethylene homopolymers and copolymers of ethylene and other monomers. The proportion of ethylene in polyethylene is, for example, 80 mol % or more. Examples of other monomers include α-olefins, vinyl acetate, acrylic esters, and the like. The α-olefin may be an olefin having a carbon number in the range of 3 to 20. Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene. Examples of polyethylene include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE), ethylene-vinyl acetate copolymer, ionomer resin, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-propylene copolymer, etc. These may be used alone or in combination of two or more.
[0025] Polypropylene is a resin containing propylene as a constituent unit, and may not contain ethylene as a constituent unit, and may be a copolymer of propylene alone or with ethylene or various α-olefins. Examples of polypropylene include homopolypropylene, block polypropylene, and random polypropylene.
[0026] The polyolefin resin may be a non-recycled polyolefin resin, a chemically recycled polyolefin resin, or a mixture thereof. The non-recycled polyolefin resin may be a petroleum-derived polyolefin resin obtained using a petroleum-derived raw material monomer, a biomass-derived polyolefin resin obtained using a biomass-derived raw material monomer, or a mixture thereof, but from the viewpoint of reducing the environmental load, a biomass-derived polyolefin resin is preferable. The chemically recycled polyolefin resin may be composed of a single chemically recycled polyolefin resin, or may be composed of a mixture of multiple types of chemically recycled polyolefin resins.
[0027] The substrate 11 may have a single layer or a multi-layer structure. In the case of a multi-layer structure, the substrate 11 is formed of two or more layers, at least one of which contains a chemically recycled resin. In addition, the substrate 11 may be a layer obtained by co-extrusion multilayer formation of a layer made of ethylene-vinyl alcohol copolymer or a layer made of polyamide using an adhesive resin or the like as necessary, and stretching the formed film. For example, a three-kind five-layer substrate made of chemically recycled resin / adhesive resin / ethylene-vinyl alcohol copolymer / adhesive resin / chemically recycled resin, a three-kind three-layer substrate made of chemically recycled resin / adhesive resin / ethylene-vinyl alcohol copolymer, a multi-layer substrate made of petroleum-derived (natural) resin / chemically recycled resin / petroleum-derived (natural) resin, or petroleum-derived (natural) resin / other polyolefin / chemically recycled resin / other resin / petroleum-derived (natural) resin, etc. may be mentioned. In the multi-layer substrate 10, the same type of material may have different specific gravities depending on the function.
[0028] The substrate 11 may further contain additives such as a filler, an antistatic agent, a plasticizer, a lubricant, a light-shielding pigment, and an antioxidant, as necessary. When the base material 11 contains a light-shielding pigment, the base material 11 can function as a light-shielding layer.
[0029] The substrate 11 may be an unstretched film or a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film. The deposition substrate 10 may be composed of either a stretched film or an unstretched film. When the substrate 11 is uniaxially stretched, it is possible to improve the tearability and heat resistance of the laminate 100. When the substrate 11 is a biaxially stretched film, it is possible to improve the mechanical strength and dimensional stability of the laminate 100.
[0030] When an adhesive layer is provided on the surface of the substrate 11, in order to enhance adhesion to the adhesive layer, the surface on the adhesive layer side may be subjected to various pretreatments such as corona treatment, plasma treatment, ozone treatment, and frame treatment, or a coating layer such as an easy-adhesion layer may be provided.
[0031] The thickness of the substrate 11 is not particularly limited and is, for example, 10 μm or more and 100 μm or less. From the viewpoint of reducing materials to reduce environmental load and from the viewpoint of obtaining excellent heat resistance, impact resistance, and gas barrier properties, the thickness of the substrate 11 may be 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, or 40 μm or more. The thickness of the substrate 11 may be 60 μm or less, or 50 μm or less.
[0032] (deposited layer) 2, the deposition layer 61 may be formed on the sealing layer 30 side of the substrate 11, or may be formed on the side of the substrate 11 opposite the sealing layer 30. The deposition layer 61 may also be formed on both sides of the substrate 11. The vapor deposition layer 61 is a layer that improves the gas barrier properties of the laminate 100, and functions as a gas barrier layer. The deposition layer 61 has a barrier property against gases such as water vapor or oxygen.
[0033] As the deposition layer 61, for example, a deposition layer of a metal or a deposition layer of an inorganic compound can be used. Metals include aluminum and silicon. Inorganic oxides include aluminum oxide and silicon oxide (silica). When the vapor-deposited layer 61 is a vapor-deposited layer of a metal such as aluminum, the vapor-deposited layer 61 can function as a light-shielding layer.
[0034] (Overcoat layer) The laminate 100 may have an overcoat layer 62 on the deposition layer 61. In this case, the gas barrier property of the laminate 100 is further improved. Therefore, when a packaging container is produced using the laminate 100 and contents are placed in the packaging container, deterioration of the contents due to gases such as oxygen can be effectively suppressed. As the overcoat layer 62, a coat layer obtained using a composition containing a water-soluble polymer and silicon alkoxide, or a coat layer made of a resin such as polyurethane can be used.
[0035] <Sealing layer> The sealing layer 30 is used to bond the sealing layers 30 together by applying heat and pressure when the laminate 100 is used to manufacture a packaging container such as a packaging bag, and a sealant film (also called a "sealant layer") or a heat seal varnish layer can be used.
[0036] The seal layer 30 preferably has a melting point lower than that of the substrate 11 disposed on the outside. In this case, when the laminate 100 is heat-sealed, it is possible to heat-seal the sealant film while suppressing melting of the substrate 11. In addition, by heating the laminate 100, the substrate 11 and the seal layer 30 can be easily separated, and material recycling can be easily performed for each of the substrate 11 and the seal layer 30.
[0037] The sealing layer 30 may further contain additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, an antistatic agent, and a light-shielding pigment, as required. When the sealing layer 30 contains a light-shielding pigment, the sealing layer 30 can function as a light-shielding layer.
[0038] The sealing layer 30 may be composed of a single layer or multiple layers. When the sealing layer 30 is composed of a single layer, the sealing layer 30 may be a recycled polyolefin resin film containing recycled resin, or may be a non-recycled polyolefin resin film. As the recycled polyolefin resin film, chemically recycled polyolefin resin is preferable because it is excellent in terms of hygiene and quality. When the plurality of layers of the sealing layer 30 is three-layered, the plurality of layers may be composed of a first outer layer, a middle layer, and a second outer layer. Here, the first outer layer and the second outer layer may be made of a non-recycled polyolefin resin film, and the intermediate layer may be made of a recycled polyolefin resin film. The seal layer 30 may be colored white or the like. For example, a white sealant containing a titanium oxide-based white pigment may be used. The seal layer 30 is not limited to a white sealant, and may be composed of a seal layer of a different color by containing a pigment other than the white pigment.
[0039] (Sealant film) The sealant film may be a polyolefin resin film or a polyester resin film. The polyolefin resin film is preferably used in terms of sealing suitability and contains a resin made of a polyolefin resin. The polyolefin resin may be the same as the resin used in the substrate 11. The polyester resin film may be a copolymer polyester obtained by copolymerizing two or more types of copolymers, and such a polyester resin film is preferable in terms of low adsorption of ingredients in the contents and flavor barrier properties.
[0040] The thickness of the sealant film is not particularly limited and is appropriately adjusted depending on the application of the laminate 100. The thickness of the sealant film may be, for example, 10 μm or more, 25 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. The thickness of the sealant film may be 100 μm or less, 80 μm or less, 60 μm or less, or 50 μm or less.
[0041] (Heat seal varnish layer) The heat seal varnish layer can be used for light packaging applications where the contents are mainly lightweight snacks. The heat seal varnish layer can be obtained by applying and drying an acrylic, elastomer, or olefin-based heat seal varnish. The heat seal varnish can be a heat seal varnish obtained by dispersing a heat seal varnish component in an aqueous solvent (e.g., water). The heat seal varnish can be, for example, an acrylic resin emulsion obtained by dispersing an acrylic resin as a heat seal varnish component in an aqueous solvent, a styrene-acrylic emulsion obtained by dispersing a styrene-acrylic copolymer resin as a heat seal varnish component in an aqueous solvent, an ionomer-based emulsion obtained by dispersing an ionomer as a heat seal varnish component in an aqueous solvent, or a polyolefin-based emulsion obtained by dispersing a polyolefin resin as a heat seal varnish component in an aqueous solvent. In particular, it is preferable to use an aqueous heat seal varnish obtained by dispersing an aqueous polyolefin resin having at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic acid ester as a heat seal varnish component in an aqueous solvent, among polyolefin emulsions. Specific examples of heat seal varnish that can be used include A450NS (acrylic type) manufactured by DIC Corporation and Chemipearl S (polyolefin type) manufactured by Mitsui Chemicals, Inc. The thickness of the heat seal varnish layer may be, for example, 0.05 μm or more, 0.5 μm or more, or 1 μm or more, and may be 20 μm or less, 10 μm or less, or 5 μm or less. The thickness of the heat seal varnish layer is preferably 1 to 5 μm. In this case, sufficient heat seal strength can be obtained and at the same time, bending resistance can be improved.
[0042] <Outer sealant layer> The outer sealant layer 40 may be the same as the sealing layer 30 described above. The thickness of the outer sealant layer 40 may be the same as or different from the thickness of the sealing layer 30. The material that makes up the outer sealant layer 40 may also be the same as or different from the material that makes up the sealing layer 30.
[0043] <Second base material> The second base material 20 is a base material that reinforces the deposition base material 10, and can further improve the strength of the laminate 100. The second base material 20 may be provided on the inside of the deposition substrate 10 (the side of the sealing layer 30) as shown in Fig. 2, or on the outside of the deposition substrate 10 (the side of the deposition substrate 10 opposite to the sealing layer 30) as shown in Fig. 4. The second base material 20 may be provided on both the inside and the outside of the deposition substrate 10. The second substrate 20 may be a film substrate made of a resin material. Examples of such resin materials include polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin resins such as polyethylene, polypropylene, and cyclic olefin copolymers COC and COP, and engineering plastics such as polystyrene, polyamides such as 66-nylon, polycarbonate, polyacrylonitrile, and polyimide. The resin material is preferably a resin material having mechanical strength and dimensional stability. The resin material is processed into a film and used as the film substrate. The film substrate may be an unstretched film or a stretched film.
[0044] The second substrate 20 may be a single layer or a laminate of multiple layers. When the second substrate 20 is configured as a single layer, the second substrate 20 may be a recycled resin film, or may be a non-recycled resin film such as a petroleum-derived resin or a biomass-derived resin. When the second substrate 20 is composed of multiple layers, all of the layers may be recycled resin films, or non-recycled resin films, or some of the layers may be non-recycled resin films and the remaining layers may be recycled resin films. When the plurality of layers is three layers, the plurality of layers may consist of a first outer layer, a middle layer, and a second outer layer. Here, the first and second outer layers may be made of non-recycled resin films, and the intermediate layer may be made of recycled resin films. In this case, the possibility that foreign matter such as impurities, gels, and aggregates will migrate from the second substrate 20 through the sealing layer 30 to the contents due to heating during retort or boiling treatment of the packaging bag can be further reduced. Therefore, the laminate 100 can be used safely to package contents such as food.
[0045] The thickness of the second substrate 20 is not particularly limited and is appropriately adjusted depending on the application of the laminate 100. The thickness of the second substrate 20 may be, for example, 10 μm or more, 25 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. The thickness of the second substrate 20 may be 100 μm or less, 80 μm or less, 60 μm or less, or 50 μm or less.
[0046] <Adhesive layer> Examples of the adhesive layer include an adhesive layer formed using an adhesive agent and an adhesive layer containing an adhesive resin (hereinafter, also referred to as an "adhesive resin layer").
[0047] Examples of the adhesive include known adhesives such as urethane adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, and isocyanate adhesives.
[0048] The adhesive may or may not contain a biomass-derived component, but from the viewpoint of reducing the environmental load, it is preferable that the adhesive contains a biomass-derived component. Specific examples of the biomass-derived component include the "DIC Dry BM Series" manufactured by DIC Corporation and the "ECOAD Series" manufactured by Toyo Ink Co., Ltd.
[0049] The adhesive may be an adhesive containing an organic solvent or an adhesive containing no organic solvent, but from the viewpoint of reducing the environmental load, an adhesive containing no organic solvent (solvent-free adhesive) is preferable.
[0050] The adhesive resin layer may be an extruded or non-extruded resin layer. The adhesive resin is a heat-sealable adhesive thermoplastic resin, and may be any resin that can melt and fuse to each other by heat. For example, acid-modified polyolefin resins obtained by modifying polyolefin resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-propylene copolymer, methylpentene polymer, polyethylene or polypropylene with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, and the like, and other resins can be used.
[0051] The thickness of the adhesive layer is not particularly limited and may be, for example, 1 μm or more. By making the thickness of the adhesive layer 1 μm or more, sufficient adhesive strength can be obtained. The thickness of the adhesive layer may be 2 μm or more. The thickness of the adhesive layer may be 50 μm or less, 5 μm or less, or 3 μm or less.
[0052] <Print layer> The printed layer 50 can be provided on one or both surfaces of the deposition substrate 10, the second substrate 20, or the outer sealant layer 40. When the printed layer 50 is provided between layers of the laminate 100, the printed layer 50 is protected by the deposition substrate 10, the second substrate 20, or the outer sealant layer 40, and therefore deterioration of the printed layer 50 can be prevented. When the printed layer 50 is the outermost layer of the laminate 100 on the side opposite to the seal layer 30, the printed layer 50 can be easily removed when recycling a package including the laminate 100 after disposal. The print layer 50 is a layer that displays characters, pictures, etc., and can be formed using ink. As the ink, for example, inks obtained by adding various pigments, plasticizers, drying agents, stabilizers, etc. to a binder resin such as a urethane-based, acrylic-based, nitrocellulose-based, or rubber-based ink can be used.
[0053] The ink may be either water-based or oil-based, but is preferably water-based. Water-based inks use water or alcohol as a solvent, and therefore can further reduce the environmental impact. In particular, when the adhesive is a solventless adhesive, the use of water-based ink as the ink can significantly reduce the environmental impact. In addition, the ink may be biomass ink or not, but from the viewpoint of reducing the environmental impact, it is preferable that the ink is biomass ink. Here, biomass ink refers to ink containing components obtained from biological resources (biomass) such as cotton, pulp, rice bran, vegetable oil, and angiosperm seeds. The ink may be recycled ink made by collecting and recycling used ink, or may be non-recycled ink. From the viewpoint of environmental impact, however, recycled ink is preferable. Furthermore, easily recyclable inks can be used. By using easily recyclable inks, it becomes easier to recycle the packaging after it has been discarded. A specific example is "SunSpectro Solvawash" manufactured by DIC Corporation.
[0054] <Gas barrier layer> The laminate 100 may further include a gas barrier layer on the substrate 11 of the deposition substrate 10 or on the second substrate 20 . The gas barrier layer is a layer that improves the gas barrier properties of the laminate 100 . The gas barrier layer includes at least one of the deposition layer 61 and the overcoat layer 62 described above.
[0055] <Other layers> The laminate 100 may further include a layer containing a non-polyolefin resin. Examples of non-polyolefin resins include polyamide resins such as nylon, and polyester resins such as polyethylene terephthalate (PET).
[0056] <Laminate> (A) Recycled resin content In the laminate 100, the content of recycled resin in the laminate 100 is preferably 10% by volume or more or 10% by mass or more. When the recycled resin content in the polyolefin resin film containing recycled resin is 100 volume % (100 mass %), the recycled resin content in the laminate 100 can be determined as the ratio of the total thickness of the film to the total thickness of the laminate 100. However, when the recycled resin content in the polyolefin resin film containing recycled resin is X mass % (less than 100 mass %) and the thickness of the film is Y1 (μm), the recycled resin content of the film thickness Y2 (μm) is calculated as X / 100×Y1 (μm). The content of recycled resin in the laminate 100 is preferably 20% by volume or more or 20% by mass or more, more preferably 25% by volume or more or 25% by mass or more, even more preferably 30% by volume or more or 30% by mass or more, and particularly preferably 40% by volume or more or 40% by mass or more.
[0057] In the present disclosure, the above-mentioned recycled resin is a chemical recycled resin and does not include material recycled resin. The chemically recycled resin may be a post-consumer recycled resin (PCR), a post-industrial recycled resin (PIR), or a mixture thereof, but is preferably a PCR. Since PCR can be secured in large quantities on the market, if the chemically recycled resin is a PCR, the cost of the laminate 100 can be reduced.
[0058] (B) Odor components In a total ion chromatogram obtained by subjecting laminate 100 to mass analysis using purge-and-trap gas chromatography-mass spectrometry, when the ratio of the peak area of nonanal as an indicator of odor components to the sum of the peak area values of all aliphatic hydrocarbon components is R1 (%) and the ratio of the peak area of decanal to the sum of the peak area values of all aliphatic hydrocarbon components is R2 (%), R1 is preferably less than 1.5%, more preferably 1.0% or less, and particularly preferably 0.5% or less. Furthermore, R2 is preferably less than 3.5%, more preferably 2.5% or less, and particularly preferably 1.5% or less. It is preferable that R1 is less than 1.5% and R2 is less than 3.5%, in which case thermal degradation is suppressed overall in the laminate 100, and the quality of the laminate 100 can be further improved. Specifically, the above mass spectrometry is carried out by cutting out a 1.0 gram sample from the laminate 100, placing this sample in a 20 mL vial together with a collector of odor components, heating it at 60°C for 1 hour to adsorb the volatile components from the sample onto the collector, and then analyzing the volatile components in the collector using a purge-and-trap gas chromatograph mass spectrometer.
[0059] (C) Fisheye Fisheyes refer to foreign matter such as gelled or charred spots that look like fish eyes and are found on film. If a fisheye has a diameter of 1 mm or more, it is considered a defective product. The number of fisheyes with a diameter of 0.5 mm or more but less than 1 mm is 100 per m 2 Less than or equal to 50 pieces / m 2 Less than 10 pieces / m 2 It would be better if it was less than this.
[0060] (D) Variation in kinetic friction On the surface of the deposition substrate 10 of the laminate 100, the variation (in-plane variation) σ of the kinetic friction force refers to the standard deviation of the kinetic friction force. σ is preferably less than 0.45, more preferably less than 0.35, and particularly preferably less than 0.2. When σ is less than 0.45, the transportability of the laminate 100 can be improved when the layer having σ of less than 0.45 is placed on the transport roller side. In addition, on the surface of the layer, there are regions where the dynamic friction force received from the transport roller is large and regions where it is small, and the difference in stress between the regions is small, so that the residual distortion in the layer is reduced, and the decrease in the strength of the laminate 100 caused by the residual distortion can be suppressed. From the viewpoint of the strength of the laminate, σ is preferably 0.1 or more, more preferably 0.2 or more, and particularly preferably 0.3 or more. The dynamic friction coefficient is measured for the laminate 100 using a multi-function static and dynamic friction tester TL201Tt (manufactured by Trinity Lab Co., Ltd.) and a tactile probe. The standard deviation σ of the dynamic friction force is a value obtained based on JIS K 7125-ISO8295, and specifically, is determined by placing the laminate 100 on a test table with the deposition substrate 10 facing down, and moving the tactile probe at a sliding speed of 10 mm / sec while contacting the laminate 100 with a load of 50 grams.
[0061] (F) Impurities The laminate 100 is analyzed by a Fourier transform infrared spectrophotometer (FT-IR: Fourier transform infrared spectroscopy) using an attenuated total reflection (ATR) measurement method. When an ATR spectrum is obtained, the 2915 cm -1 Absorption coefficients of CH inverse symmetric stretching of methylene groups near 1720 cm from polyesters and polyurethanes -1 The ratio R3 of the absorption coefficients for C=O stretching near the polyolefin is preferably less than 0.1, more preferably less than 0.05, and particularly preferably 0.01 or less, as an index showing that there are few resin components other than polyolefin. In the above analysis, a diamond prism is used as the prism to be brought into close contact with the laminate 100, and the angle of incidence with respect to the surface of the laminate 100 is set to 45°.
[0062] When the laminate 100 includes a deposition substrate 10 and a sealing layer 30, both the deposition substrate 10 and the sealing layer 30 may be recycled resin films.
[0063] <<Packaged goods>> Next, an embodiment of a packaging article according to another aspect of the present disclosure will be described with reference to Fig. 5. Fig. 5 is a cross-sectional view showing one embodiment of a packaging article according to another aspect of the present disclosure.
[0064] As shown in FIG. 5, the packaged article 500 includes a packaging bag 400 as a packaging container, and a content C accommodated in the packaging bag 400. The packaging bag 400 is obtained by using a pair of laminates 100. The packaging bag 400 is obtained, for example, by facing the seal layers 30 of the pair of laminates 100 to each other and adhering the peripheral portions. The packaging bag 400 is composed of a storage section that accommodates the content C, and an adhesive section provided around the storage section. The adhesive section is a portion formed by adhering the seal layers 30 of the opposing laminates 100 to each other, and the storage section is a portion where the seal layers 30 of the opposing laminates 100 are not adhered to each other.
[0065] According to the packaging article 500, the chemically recycled resin contained in the substrate 11 of the laminate 100 is a recycled resin produced by first converting a discarded resin into a low molecular weight resin through a process of converting the resin into a monomer through gasification, oilification, and refined naphtha, or a process of converting the resin into a monomer through depolymerization, which is performed according to the material characteristics, and then polymerizing the resin. For this reason, the chemically recycled resin is less likely to be mixed with foreign matter such as impurities, gels, and aggregates, compared with the material recycled resin, which is a resin obtained by cleaning and crushing a resin product such as a recovered used packaging material, and then heating and melting the resin product to re-materialize it. In addition, unlike the material recycled resin, the chemically recycled resin is not affected by heat treatment such as heating and melting after the recycling process, so that it is less likely to be thermally deteriorated, and there is less presence of foreign matter such as gels and aggregates on the surface. For this reason, even if a deposition layer 61 is formed on such a substrate 11, the thickness of the deposition layer 61 is less likely to be uneven, and a high-quality deposition layer 61 is formed. Therefore, the packaging bag 400 obtained by using the packaging laminate 100 can suppress the deterioration of the gas barrier property even when using the deposition base material 10 formed by forming the deposition layer 61 on the base material 11 containing recycled resin. Therefore, the packaging article 500 having the packaging container 400 can suppress the deterioration of the gas barrier property. In addition, since the packaging article 500 can suppress the deterioration of the gas barrier property, the packaging article 500 can suppress the deterioration of the quality of the contents C such as food due to gas, and can safely store the contents C. In addition, since the laminate 100 can improve the quality, the packaging article 500 including the packaging bag 400 obtained by using the packaging laminate 100 can improve the properties such as strength.
[0066] (Contents) The contents C are not particularly limited and may be appropriately selected depending on the application of the packaging bag 400. The contents C are not particularly limited, and examples of the contents C include food, shampoo, rinse, body soap, detergent, and the like.
[0067] (packaging bag) The pair of laminates 100 constituting the packaging bag 400 may have the same configuration as each other, or may have different configurations from each other.
[0068] The packaging bag 400 may have a half-cut line, and may further have an easy-open processed part at both ends or one end of the half-cut line. Examples of the easy-open processed part include a group of scars, and a V-shaped, U-shaped, or I-shaped notch.
[0069] In the adhesive portion of the packaging bag 400, the seal layers 30 of the pair of laminates 100 may be directly attached to each other by heat sealing (see FIG. 5), or may be attached to each other by an adhesive.
[0070] (Method of manufacturing packaging articles) Next, an example of a method for producing a packaged article 500 using the laminate 100 will be described.
[0071] First, a pair of laminates 100 is prepared. Then, the seal layers 30 of the pair of laminates 100 are placed opposite each other, and the seal layers 30 are bonded together. At this time, a part of the periphery of the laminate is bonded to form a U-shape to form a bonded part, and a part that is not bonded (unbonded part) is also formed. In this way, a packaging bag having an opening formed by the unbonded part is obtained.
[0072] Next, the contents C are filled in through the opening of the packaging bag. Thereafter, the seal layers 30 of the laminate 100 are bonded together at the unbonded portions, so that the unbonded portions also become bonded portions. In this manner, a packaged article 500 including the packaging bag 400 and the contents C contained therein can be manufactured.
[0073] Although the preferred embodiments of the present disclosure have been described above, the present disclosure is not limited to the above embodiments. For example, in the packaged article 500 shown in Fig. 5, the packaging bag 400 is formed using a pair of laminates 100, but the packaging bag may be manufactured by folding one laminate 100 with the seal layer 30 on the inside and bonding the overlapping peripheral portions together.
[0074] 5, the packaging bag 400 may be a standing pouch-shaped packaging bag, a two-sided bag, a three-sided bag, a four-sided bag, a palm-shaped bag, or a gusset bag. The packaging bag 400 may be provided with a stopper or a synthetic resin fastener that can be repeatedly sealed by fitting a strip-shaped protrusion and a strip-shaped groove.
[0075] In the above embodiment, the packaging container is a packaging bag, but the packaging container may be a tube container. When the packaging container is a tube container, the laminate 100 includes an outer sealant layer 40 that is adhered to the deposition substrate 10. Furthermore, when the packaging bag is used for packaging sweets and the like (light packaging), a bag made using a heat seal varnish layer as the seal layer of the laminate 100 can be used as the packaging bag. Specifically, a laminate in which a deposition layer made of a metal or inorganic oxide is provided on a substrate, and a heat seal varnish layer is provided directly on the deposition layer can be used as the packaging bag.
[0076] The embodiments of the present disclosure have been described above, and the outline of the present disclosure is as follows. [1] A deposition substrate having a deposition layer formed on a substrate, The substrate is a polyolefin resin film containing recycled resin, The deposition substrate, wherein the recycled resin is a chemically recycled resin. [2] A laminate for packaging material comprising the deposition base material according to [1] and a seal layer. [3] The laminate for packaging materials according to [2], wherein the content of the recycled resin in the laminate for packaging materials is 10% by volume or more or 10% by mass or more. [4] The laminate for packaging materials according to [2] or [3], further comprising a second substrate on one or both sides of the substrate. [5] The laminate for packaging materials according to any one of [2] to [4], wherein the recycled resin is a post-consumer recycled resin. [6] The laminate for packaging materials according to any one of [2] to [5], wherein the sealing layer comprises a sealant film or a heat seal varnish layer. [7] The laminate for packaging materials according to [4], wherein the deposition substrate and the second substrate are bonded together with a solventless adhesive. [8] The laminate for packaging materials according to any one of [1] to [7], further comprising an overcoat layer on the vapor deposition layer. [9] Further comprising an adhesive layer between the substrate and the seal layer; The laminate for packaging materials according to any one of [2] to [8], wherein the adhesive layer is an adhesive layer formed using an adhesive, and the adhesive is a urethane-based adhesive, a polyester-based adhesive, a polyamide-based adhesive, an epoxy-based adhesive, or an isocyanate-based adhesive.
[10] A packaging container obtained by using the laminate for packaging material according to any one of [2] to [9].
[11]
[10] A packaging container according to the present invention; and a content contained within the packaging container. EXAMPLES
[0077] The present disclosure will be described more specifically with reference to the following examples, but the present disclosure is not limited to these examples.
[0078] Example 1 A chemically recycled low-density polyethylene (PCR ChemiR 100%-LDPE) film (thickness 35 μm) was prepared as the substrate, and a petroleum-derived LDPE film (thickness 60 μm) was prepared as the sealing layer. Note that "PCR ChemiR 100%-LDPE" means that the content of post-consumer chemical recycled resin (PCR ChemiR) in the substrate is 100% by volume (100% by mass). Then, a SiOx deposition layer (10 nm thick) was formed on the substrate to obtain a deposition substrate, and an overcoat layer (0.3 μm thick) was formed on the deposition layer. The overcoat layer was formed by mixing a hydrolysis solution (A solution) with a solid content of 3 wt% (SiO2 equivalent) obtained by adding 89.6 g of hydrochloric acid (0.1 N) to 10.4 g of tetraethoxysilane [Si(OC2H5)4: hereinafter referred to as "TEOS") and stirring for 30 minutes, and a 3.0 wt% water / isopropyl alcohol solution (water:isopropyl alcohol weight ratio 90:10) (B solution) of polyvinyl alcohol in a mixing ratio (weight ratio) of A solution / B solution of 60 / 40, applying the coating agent with a bar coater and drying it with a dryer at 120°C for 1 minute. Next, a printing layer was formed on the overcoat layer of the deposition base material using aqueous flexographic ink. After that, a dry lamination adhesive (urethane adhesive) was applied to the surface of the printing layer to form an adhesive layer with a thickness of 3 μm (dry film thickness), and a seal layer was attached to the adhesive layer to produce a packaging laminate (deposition base material (base material / deposition layer) / overcoat layer / printing layer / adhesive layer / seal layer).
[0079] Example 2 A laminate for packaging material (vapor-deposited substrate (substrate / vapor-deposited layer) / overcoat layer / printed layer / adhesive layer / sealing layer) was produced in the same manner as in Example 1, except that the substrate was changed from a PCR Chemi-R 100%-LDPE film (35 μm thick) to a PCR Chemi-R 100%-LDPE film (25 μm thick), the sealing layer was changed from a petroleum-derived LDPE film (60 μm thick) to a biomass-derived LDPE film (60 μm thick), the adhesive for dry lamination (urethane-based adhesive) was changed to a 1.5 μm-thick solventless adhesive (polyester-based), and the SiOx vapor-deposited layer (10 nm thick) was changed to an aluminum oxide vapor-deposited layer (10 nm thick).
[0080] Example 3 A chemically recycled low-density polyethylene (PCR Chemical 100%-LDPE) film (thickness 35 μm) was prepared as the substrate. Note that "PCR Chemical 100%-LDPE" means that the content of post-consumer chemical recycled resin (PCR Chemical) in the substrate is 100% by volume (100% by mass). Then, a SiOx vapor-deposited layer (thickness: 10 nm) was formed on the substrate to form a vapor-deposited substrate, and then an overcoat layer (thickness: 0.3 μm) was formed on the vapor-deposited layer in the same manner as in Example 1. Next, a printing layer was formed on the overcoat layer using water-based flexographic ink, and then a polyolefin-based heat seal varnish was applied to the surface of the printing layer and dried to form a seal layer (thickness 1 μm) to produce a laminate for packaging material (substrate / printed layer / seal layer). At this time, a water-based polyolefin dispersion (Chemipearl S manufactured by Mitsui Chemicals, Inc.) was used as the polyolefin-based heat seal varnish.
[0081] Example 4 A chemically recycled high density polyethylene (PCR ChemiR 100%-HDPE) film (thickness 25 μm) was prepared as the substrate, a petroleum-derived LDPE film (thickness 50 μm) was prepared as the sealing layer, and a petroleum-derived stretched high density polyethylene (HDPE) film (thickness 15 μm) was prepared as the second substrate. Note that "PCR ChemiR 100%-HDPE" means that the content of post-consumer chemical recycled resin (PCR ChemiR) in the substrate is 100% by volume (100% by mass). Then, a SiOx vapor-deposited layer (thickness: 10 nm) was formed on the substrate to form a vapor-deposited substrate, and then an overcoat layer (thickness: 0.3 μm) was formed on the vapor-deposited layer in the same manner as in Example 1. Next, a printing layer was formed on the overcoat layer using water-based flexographic ink, and then a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the printing layer to form a first adhesive layer with a thickness of 3 μm (dry film thickness), and a sealing layer was bonded to the first adhesive layer. Finally, a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the substrate of the vapor deposition substrate to form a second adhesive layer with a thickness of 3 μm (dry film thickness), and a second substrate was bonded to the second adhesive layer to produce a laminate for packaging material (second substrate / first adhesive layer / vapor deposition substrate (substrate / vapor deposition layer) / overcoat layer / printing layer / second adhesive layer / sealing layer).
[0082] Example 5 A chemically recycled low-density polyethylene (PCR ChemiR 100%-LDPE) film (50 μm thick) was prepared as the substrate, a petroleum-derived LDPE film (80 μm thick) was prepared as the sealing layer, and a petroleum-derived LDPE film (80 μm thick) was prepared as the outer sealant layer. Note that "PCR ChemiR 100%-LDPE" means that the content of post-consumer chemical recycled resin (PCR ChemiR) in the substrate is 100% by volume (100% by mass). Then, a SiOx vapor-deposited layer (thickness: 10 nm) was formed on the substrate to form a vapor-deposited substrate, and then an overcoat layer (thickness: 0.3 μm) was formed on the vapor-deposited layer in the same manner as in Example 1. Next, a printing layer was formed on the overcoat layer using water-based flexographic ink, and then a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the printing layer to form a first adhesive layer with a thickness of 3 μm (dry film thickness), and a sealing layer was bonded to the first adhesive layer. Finally, a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the substrate of the vapor deposition substrate to form a second adhesive layer with a thickness of 3 μm (dry film thickness), and an outer sealant layer was bonded to the second adhesive layer to produce a laminate for packaging material (outer sealant layer / first adhesive layer / vapor deposition substrate (substrate / vapor deposition layer) / overcoat layer / printing layer / second adhesive layer / sealing layer).
[0083] Example 6 As the substrate, a PCR ChemiR 100%-OPP film (50 μm thick) was prepared, as the sealing layer, a petroleum-derived LDPE film (80 μm thick) was prepared, and as the outer sealant layer, a petroleum-derived LDPE film (80 μm thick) was prepared. Note that "PCR ChemiR 100%-OPP" means that the content of post-consumer chemical recycled resin (PCR ChemiR) in the substrate is 100% by volume (100% by mass). Then, a SiOx vapor-deposited layer (thickness: 10 nm) was formed on the substrate to form a vapor-deposited substrate, and then an overcoat layer (thickness: 0.3 μm) was formed on the vapor-deposited layer in the same manner as in Example 1. Next, a printing layer was formed on the overcoat layer using water-based flexographic ink, and then a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the printing layer to form a first adhesive layer with a thickness of 3 μm (dry film thickness), and a sealing layer was bonded to the first adhesive layer. Finally, a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the substrate of the vapor deposition substrate to form a second adhesive layer with a thickness of 3 μm (dry film thickness), and an outer sealant layer was bonded to the second adhesive layer to produce a laminate for packaging material (outer sealant layer / first adhesive layer / vapor deposition substrate (substrate / vapor deposition layer) / overcoat layer / printing layer / second adhesive layer / sealing layer).
[0084] Example 7 As the substrate, a PCR ChemiR 100%-OPP film (thickness 25 μm) was prepared, as the seal layer, a petroleum-derived unstretched polypropylene (CPP) film (thickness 50 μm) was prepared, and as the second substrate, a PCR ChemiR 100%-OPP film (thickness 25 μm) was prepared. Note that "PCR ChemiR 100%-OPP" means that the content of post-consumer chemical recycled resin (PCR ChemiR) in the substrate is 100% by volume (100% by mass). Then, a SiOx vapor-deposited layer (thickness: 10 nm) was formed on the substrate to form a vapor-deposited substrate, and then an overcoat layer (thickness: 0.3 μm) was formed on the vapor-deposited layer in the same manner as in Example 1. Next, a printing layer was formed on the overcoat layer using water-based flexographic ink, and then a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the printing layer to form a first adhesive layer with a thickness of 3 μm (dry film thickness), and a sealing layer was bonded to the first adhesive layer. Finally, a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the substrate of the vapor deposition substrate to form a second adhesive layer with a thickness of 3 μm (dry film thickness), and a second substrate was bonded to the second adhesive layer to produce a laminate for packaging material (second substrate / first adhesive layer / vapor deposition substrate (substrate / vapor deposition layer) / overcoat layer / printing layer / second adhesive layer / sealing layer).
[0085] Example 8 As the substrate, a PCR ChemiR 100%-OPP film (thickness 25 μm) was prepared, as the sealing layer, a petroleum-derived LDPE film (thickness 60 μm) was prepared, and as the second substrate, a PCR ChemiR 100%-OPP film (thickness 25 μm) was prepared. Note that "PCR ChemiR 100%-OPP" means that the content of post-consumer chemical recycled resin (PCR ChemiR) in the substrate is 100% by volume (100% by mass). Then, a SiOx vapor-deposited layer (thickness: 10 nm) was formed on the substrate to form a vapor-deposited substrate, and then an overcoat layer (thickness: 0.3 μm) was formed on the vapor-deposited layer in the same manner as in Example 1. Next, a printing layer was formed on the overcoat layer using water-based flexographic ink, and then a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the printing layer to form a first adhesive layer with a thickness of 3 μm (dry film thickness), and a sealing layer was bonded to the first adhesive layer. Finally, a dry lamination adhesive (urethane-based adhesive) was applied to the surface of the substrate of the vapor deposition substrate to form a second adhesive layer with a thickness of 3 μm (dry film thickness), and a second substrate was bonded to the second adhesive layer to produce a laminate for packaging material (second substrate / first adhesive layer / vapor deposition substrate (substrate / vapor deposition layer) / overcoat layer / printing layer / second adhesive layer / sealing layer).
[0086] Comparative Example 1 A low-density polyethylene (PCRMR100%-LDPE) film (thickness 25 μm) made from recycled materials using used polyethylene bags was prepared as the substrate, and a petroleum-derived LDPE film (thickness 60 μm) was prepared as the sealing layer (sealant layer). Note that "PCR ChemiR 100%-LDPE" means that the content of post-consumer mechanically recycled resin (PCRMR) in the deposition substrate is 100% by volume (100% by mass). Then, a deposition layer (10 nm thick) made of aluminum oxide was formed on one side of the substrate to obtain a deposition substrate, and an overcoat layer (0.3 μm thick) was formed on the deposition layer. The overcoat layer was formed by mixing a hydrolysis solution (A solution) with a solid content of 3 wt% (SiO2 equivalent) (SiO2 equivalent) obtained by adding 89.6 g of hydrochloric acid (0.1 N) to 10.4 g of tetraethoxysilane [Si(OC2H5)4: hereinafter referred to as "TEOS") and stirring for 30 minutes, and a 3.0 wt% water / isopropyl alcohol solution (water:isopropyl alcohol weight ratio 90:10) (B solution) of polyvinyl alcohol in a mixing ratio (weight ratio) of A solution / B solution of 60 / 40, applying the coating agent with a bar coater and drying it with a dryer at 120°C for 1 minute. Next, a printing layer was formed on the overcoat layer of the vapor deposition base material using aqueous flexographic ink, and a dry laminate adhesive (urethane-based adhesive) was applied to the surface of the printing layer to form an adhesive layer with a thickness of 3 μm (dry film thickness). A seal layer was then bonded to the adhesive layer to produce a packaging laminate (vapor deposition base material (base material / vapor deposition layer) / overcoat layer / printing layer / adhesive layer / seal layer).
[0087] Comparative Example 2 The substrate was changed from a PCRMR100%-LDPE film (thickness 25 μm) to a low-density polyethylene (PCRMR40%-LDPE) film (thickness 60 μm) obtained by washing used polyethylene bags and mixing low-density polyethylene (PCRMR-LDPE) pellets obtained by mechanical recycling and petroleum-derived LDPE pellets in a ratio of 40:60 (mass ratio), the seal layer (sealant layer) was changed from a petroleum-derived LDPE film (thickness 60 μm) to a petroleum-derived LDPE film (thickness 50 μm), and the aluminum oxide vapor deposition layer (thickness 10 nm) was changed to a SiOx vapor deposition layer (thickness 10 nm). Except for this, a laminate for packaging material (vapor deposition substrate (substrate / vapor deposition layer) / overcoat layer / printing layer / adhesive layer / seal layer) was produced in the same manner as in Comparative Example 1. Note that "PCRMR40%-LDPE" means that the content of post-consumer mechanically recycled resin (PCRMR) in the substrate is 40% by mass. In this case, the volume of the layer made of recycled material can be calculated by taking into account the density of the mixed resin, and this can be used to calculate the film thickness ratio. Note that the density of the mixed resins is the same, and the mass% is also the volume%. In addition, the density of the PCRMR-LDPE40% film used as the substrate is low (0.920 g / cm 3 ) was decided.
[0088] Comparative Example 3 A PCRMR100%-LDPE film (thickness 25 μm) was prepared as the substrate, a PCRMR100%-LDPE film (thickness 25 μm) was prepared as the second substrate, and a petroleum-derived LDPE film (thickness 60 μm) was prepared as the sealing layer (sealant layer). Then, a deposition layer (10 nm thick) made of aluminum oxide was formed on one side of the substrate to obtain a deposition substrate, and an overcoat layer (0.3 μm thick) was formed on the deposition layer. The overcoat layer was formed by mixing a hydrolysis solution (liquid A) of 3 wt% solids (SiO2 equivalent) (10.4 g of tetraethoxysilane [Si(OC2H5)4: hereinafter referred to as "TEOS") with 89.6 g of hydrochloric acid (0.1 N) and stirring for 30 minutes to hydrolyze the solution, and a 3.0 wt% water / isopropyl alcohol solution (water:isopropyl alcohol weight ratio 90:10) (liquid B) of polyvinyl alcohol in a mixing ratio (weight ratio) of 60 / 40. The coating agent was applied with a bar coater and dried in a dryer at 120°C for 1 minute. Meanwhile, a printed layer was formed on one surface of the second substrate using water-based flexographic ink, and a laminating adhesive (urethane-based adhesive) was applied to the surface of the printed layer to form a first adhesive layer having a thickness of 3 μm (dry film thickness). Then, the overcoat layer on the deposition base material was bonded to the first adhesive layer. Next, a dry lamination adhesive (urethane adhesive) was applied to the base material of the deposition base material to form a second adhesive layer with a thickness of 3 μm (dry film thickness), and the second adhesive layer was bonded to the seal layer to produce a packaging laminate (second base material / printing layer / first adhesive layer / overcoat layer / deposition base material (deposition layer / base material) / second adhesive layer / seal layer).
[0089] Comparative Example 4 The substrate was a low-density polyethylene (PCRMR-LLDPE 100%) film (thickness 35 μm) that had been material-cycled using used packaging material (nylon / printed layer / PET layer / aluminum vapor deposition layer / linear low-density polyethylene (LLDPE) sealant layer), and a petroleum-derived LDPE film (thickness 60 μm) was prepared as the sealing layer (sealant layer). Then, a deposition layer (10 nm thick) made of aluminum oxide was formed on one side of the substrate to obtain a deposition substrate, and an overcoat layer (0.3 μm thick) was formed on the deposition layer. The overcoat layer was formed by mixing a hydrolysis solution (liquid A) of 3 wt% solids (SiO2 equivalent) (10.4 g of tetraethoxysilane [Si(OC2H5)4: hereinafter referred to as "TEOS") with 89.6 g of hydrochloric acid (0.1 N) and stirring for 30 minutes to hydrolyze the solution, and a 3.0 wt% water / isopropyl alcohol solution (water:isopropyl alcohol weight ratio 90:10) (liquid B) of polyvinyl alcohol in a mixing ratio (weight ratio) of 60 / 40. The coating agent was applied with a bar coater and dried in a dryer at 120°C for 1 minute. Furthermore, a printing layer was formed on the overcoat layer on the vapor-deposited substrate using aqueous flexographic ink, and a laminating adhesive (urethane-based adhesive) was applied to the surface of the printed surface to form an adhesive layer with a thickness of 3 μm (dry film thickness). A sealing layer was then bonded to the adhesive layer to produce a laminate for packaging material (vapor-deposited substrate (substrate / vapor-deposited layer) / overcoat layer / printed layer / adhesive layer / sealing layer).
[0090] Comparative Example 5 As the substrate, a low-density polyethylene film (PCRMR-HDPE-LLDPE100%) (thickness 25 μm) that was material-cycled using used packaging materials (high-density polyethylene (HDPE) layer / printed layer / HDPE layer / LLDPE sealant layer) was prepared, and as the sealant layer, a petroleum-derived LDPE film (thickness 60 μm) was prepared. Note that "PCRMR-HDPE-LLDPE100%" means that the total content of mechanically recycled high-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE) in the vapor-deposited substrate is 100% by volume (100% by mass). Then, a deposition layer (10 nm thick) made of aluminum oxide was formed on one side of the substrate to obtain a deposition substrate, and an overcoat layer (0.3 μm thick) was formed on the deposition layer. The overcoat layer was formed by mixing a hydrolysis solution (liquid A) of 3 wt% solids (SiO2 equivalent) (10.4 g of tetraethoxysilane [Si(OC2H5)4: hereinafter referred to as "TEOS") with 89.6 g of hydrochloric acid (0.1 N) and stirring for 30 minutes to hydrolyze the solution, and a 3.0 wt% water / isopropyl alcohol solution (water:isopropyl alcohol weight ratio 90:10) (liquid B) of polyvinyl alcohol in a mixing ratio (weight ratio) of 60 / 40. The coating agent was applied with a bar coater and dried in a dryer at 120°C for 1 minute. Furthermore, a printing layer was formed on the overcoat layer on the vapor-deposited substrate using aqueous flexographic ink, and a laminating adhesive (urethane-based adhesive) was applied to the surface of the printed surface to form an adhesive layer with a thickness of 3 μm (dry film thickness). A sealing layer was then bonded to the adhesive layer to produce a laminate for packaging material (vapor-deposited substrate (substrate / vapor-deposited layer) / overcoat layer / printed layer / adhesive layer / sealing layer).
[0091] Comparative Example 6 A laminate for packaging material (vapor deposition substrate (substrate / vapor deposition layer) / overcoat layer / printing layer / adhesive layer / sealing layer) was prepared in the same manner as in Comparative Example 1, except that the sealing layer (sealant layer) was changed from a petroleum-derived LDPE film (thickness 50 μm) to a petroleum-derived LDPE film (thickness 60 μm).
[0092] (Reference example 1) A petroleum-derived LDPE film (thickness 25 μm) was prepared as the substrate, and a petroleum-derived LLDPE film (thickness 60 μm) was prepared as the sealing layer (sealant layer). Then, a deposition layer (10 nm thick) made of aluminum oxide was formed on one side of the substrate to obtain a deposition substrate, and an overcoat layer (0.3 μm thick) was formed on the deposition layer. The overcoat layer was formed by mixing a hydrolysis solution (liquid A) of 3 wt% solids (SiO2 equivalent) (10.4 g of tetraethoxysilane [Si(OC2H5)4: hereinafter referred to as "TEOS") with 89.6 g of hydrochloric acid (0.1 N) and stirring for 30 minutes to hydrolyze the solution, and a 3.0 wt% water / isopropyl alcohol solution (water:isopropyl alcohol weight ratio 90:10) (liquid B) of polyvinyl alcohol in a mixing ratio (weight ratio) of 60 / 40. The coating agent was applied with a bar coater and dried in a dryer at 120°C for 1 minute. Next, a printing layer was formed on the overcoat layer on the vapor-deposited substrate using an aqueous flexographic ink, and a laminating adhesive (urethane-based adhesive) was applied to the surface of the printed surface to form an adhesive layer with a thickness of 3 μm (dry film thickness). A sealing layer was then bonded to the adhesive layer to produce a laminate for packaging material (vapor-deposited substrate (substrate / vapor-deposited layer) / overcoat layer / printed layer / adhesive layer / sealing layer).
[0093] <Recycled resin content> For the laminates for packaging materials of the Examples, Comparative Examples and Reference Examples prepared as described above, the content of recycled resin in the laminates for packaging materials was calculated based on the following formula. Recycled resin content = 100 x total thickness of layers containing recycled resins / total thickness of laminate for packaging material However, when the layer containing recycled resin is a layer containing recycled resin and petroleum-derived resin, the value obtained by multiplying the thickness of this layer by the content (mass%) of recycled resin in the layer was used as the thickness value of the layer containing recycled resin. In addition, since the thicknesses of the printed layer, the vapor deposition layer and the overcoat layer are quite small, they were not taken into consideration when determining the recycled resin content in the laminate.
[0094] <Evaluation> The laminates for packaging materials of the Examples, Comparative Examples and Reference Examples prepared as described above were evaluated as follows: Evaluation 1 (generation of odorous components), Evaluation 2 (fish eyes), Evaluation 3 (impurities), Evaluation 4 (variation in dynamic friction force) and Evaluation 5 (gas barrier properties). Here, Evaluation 1 is an evaluation on quality, and Evaluations 2 and 3 are evaluations on hygiene.
[0095] (1) Rating 1 (Odor component generation) First, the laminate for packaging materials was analyzed using purge-and-trap gas chromatography mass spectrometry. Specifically, a 1.0 gram sample was cut out from the laminate for packaging materials, and this sample was placed in a 20 mL vial together with a collector for odor components, and heated at 60°C for 1 hour to adsorb the volatile components from the sample onto the collector. The volatile components in the collector were then analyzed using a purge-and-trap gas chromatography mass spectrometry device, and a total ion chromatogram was obtained. Next, in the total ion chromatogram obtained as described above, the ratio R1 of the peak area of nonanal to the sum of the peak area values of all the aliphatic hydrocarbon components, and the ratio R2 of the peak area of decanal to the sum of the peak area values of all the aliphatic hydrocarbon components, as indicators of odor components, were calculated. The evaluation was carried out based on the following evaluation criteria. The results are shown in Tables 1 to 3. (Evaluation Criteria) ◎ R1 is less than 1.5% and R2 is less than 0.35% ○ R1 is less than 1.5% and R2 is 0.35% or more, or R1 is 1.5% or more and R2 is less than 0.35% × R1 is 1.5% or more and R2 is 0.35% or more
[0096] (2) Rating 2 (Fisheye) A sample measuring 1 m x 1 m was cut out from the packaging laminate, and the sample was placed on a black table with the seal layer side facing down. Protrusions (protruding foreign matter) with a diameter of 0.5 mm or more and less than 1 mm were counted visually as fisheye 1, and protrusions (protruding foreign matter) with a diameter of 1 mm or more were counted visually as fisheye 2, and the number of protrusions (protruding foreign matter) was counted visually as fisheye 2, and the evaluation was performed based on the following evaluation criteria. The results are shown in Tables 1 to 3. (Evaluation Criteria) ◎ N1 is 10 or less and N2 is 0 ○ N1 is 11 to 99 and N2 is 0 × N1 is 100 or more or N2 is 1 or more
[0097] (3) Rating 3 (impurities) The laminate for packaging material was analyzed by Fourier transform infrared spectroscopy (FT-IR) using attenuated total reflection (ATR) to obtain an ATR spectrum. At this time, a diamond prism was used as the prism to be attached to the laminate for packaging material, and the angle of incidence to the surface of the laminate for packaging material was set to 45°. In addition, the 2915 cm spectrum of polyethylene is -1 Absorption coefficients of CH inverse symmetric stretching of methylene groups near 1720 cm from polyesters and polyurethanes -1 The ratio R3 of the absorption coefficients of the C═O stretching near the nucleus was calculated, and the results were evaluated based on the following criteria. The results are shown in Tables 1 to 3. (Evaluation Criteria) ◎ R3 is less than 0.05 ○ R3 is 0.05 or more and less than 0.1 × R3 is 0.1 or more
[0098] (4) Rating 4 (variation in dynamic friction force) The kinetic friction force of the laminate for packaging materials was measured using a multi-function static and kinetic friction tester TL201Tt (manufactured by Trinity Lab Co., Ltd.) and a tactile tester. Specifically, the packaging laminate was placed on a test table with the sealant layer facing down, and a tactile probe was moved at a sliding speed of 10 mm / sec while being in contact with the packaging laminate (on the deposition substrate side) with a load of 50 grams, and the standard deviation of the dynamic frictional force was obtained, and this standard deviation σ of the dynamic frictional force was taken as the variation in the dynamic frictional force. Evaluation was then performed based on the following evaluation criteria. The results are shown in Tables 1 to 3. (Evaluation Criteria) A σ is less than 0.35 B σ is 0.35 or more and less than 0.45 C σ is 0.45 or more (5) Rating 5 (gas barrier properties) The gas barrier properties of the laminate for packaging material were evaluated as follows. Specifically, the oxygen permeability (unit: cc / m 2 The oxygen permeability (Oxygen permeability) was measured by JIS K7126, Method B (isobaric method) and the oxygen permeability was used as an index of gas barrier properties. The measurement was performed using a MOCON OXTRAN 2 / 20 instrument at a temperature of 30°C and a relative humidity of 70%. (Evaluation Criteria) A: Oxygen permeability is 1cc / (m 2 ·day·atm). B: Oxygen permeability is 1cc / (m 2 ·day · atm) or more, 10cc / (m 2 ·day·atm). C: Oxygen permeability is 10cc / (m 2 ·day·atm).
[0099] [Table 1] [Table 2] [Table 3]
[0100] From the results shown in Tables 1 to 3, all of the packaging laminates of Examples 1 to 8, even when using a deposition base material having a substrate containing recycled resin, hardly generated odorous components, had little foreign matter or impurities such as gels and aggregates, and had good gas barrier properties, and had performance equivalent to that of the packaging laminate of Reference Example 1. In contrast, in the packaging laminates of Comparative Examples 1 to 5, which used material recycled resin, when the recycled resin content was increased to 10 volume % or more, at least one of the following occurred: an increased amount of odorous components was generated, an increased number of fish eyes was generated, and an increased amount of impurities was generated; the gas barrier properties were poor, and the performance was not equivalent to that of the packaging laminate of Reference Example 1.
[0101] From the above, it has been confirmed that, according to the laminate for packaging material of the present disclosure, even when a vapor deposition base material in which a vapor deposition layer is formed on a base material containing recycled resin is used, deterioration of gas barrier properties can be suppressed. [Explanation of symbols]
[0102] Reference Signs List 10... deposition substrate, 11... substrate, 20... second substrate, 30... seal layer, 61... deposition layer, 62... overcoat layer, 100... laminate, 400... packaging bag (packaging container), 500... packaging article, C... contents.
Claims
1. A deposition substrate having a deposition layer formed on a substrate, The substrate is a polyolefin resin film containing recycled resin, The vapor-deposited substrate, wherein the recycled resin is a chemically recycled resin.
2. A laminate for packaging material comprising the deposition base material according to claim 1 and a seal layer, Further comprising an adhesive layer between the substrate and the seal layer; The adhesive layer is an adhesive layer formed using an adhesive, and the adhesive is a urethane-based adhesive, a polyester-based adhesive, a polyamide-based adhesive, an epoxy-based adhesive, or an isocyanate-based adhesive.
Citation Information
Patent Citations
Flexible pouches using post-consumer resins
JP2022552096A
Material-recycled pe-containing film and package including the same
JP2023040660A